Targeting DMPK with Antisense Oligonucleotide Improves Muscle Strength in Myotonic Dystrophy Type 1 Mice - Jauvin, Dominic (Mol Ther Nucleic Acids, 2017)
Myotonic dystrophy type 1 (DM1), a dominant hereditary muscular dystrophy, is caused by an abnormal expansion of a (CTG)(n) trinucleotide repeat in the 3′ UTR of the human dystrophia myotonica protein kinase (DMPK) gene. As a consequence, mutant transcripts containing expanded CUG repeats are retained in nuclear foci and alter the function of splicing regulatory factors members of the MBNL and CELF families, resulting in alternative splicing misregulation of specific transcripts in affected DM1 tissues. In the present study, we treated DMSXL mice systemically with a 2′-4′-constrained, ethyl-modified (ISIS 486178) antisense oligonucleotide (ASO) targeted to the 3′ UTR of the DMPK gene, which led to a 70% reduction in CUG(exp) RNA abundance and foci in different skeletal muscles and a 30% reduction in the heart. Furthermore, treatment with ISIS 486178 ASO improved body weight, muscle strength, and muscle histology, whereas no overt toxicity was detected. This is evidence that the reduction of CUG(exp) RNA improves muscle strength in DM1, suggesting that muscle weakness in DM1 patients may be improved following elimination of toxic RNAs.